Timing of Measles, Mumps, and Rubella Vaccination: Secondary Outcomes from an Immunological Survey - Jana Zibolenová; Romana Ulbrichtová; Eva Malobická; Martin Novák; Tibor Baška; Lucia Časnocha Lúčanová; Ján Mikas; Adriana Mečochová; Henrieta Hudečková (Vaccines)
Background/Objectives: This study analyzed data on the actual timing of the first and second doses of the Measles, Mumps, and Rubella (MMR) vaccination in Slovakia according to the vaccination schedule. Methods: Histograms were constructed using immunological survey data on MMR vaccination conducted in Slovakia in 2018. Results: For the first dose (2560 individuals), 83.4% of them were vaccinated timely (15th–18th month, mostly in the 16th month), while 13.8% of them were delayed. For the second dose (1061 individuals), 72.7% of vaccinations were timely (11th year), and 23.2% were delayed. There was a bimodal distribution of the timing of the administration of the second dose, with peaks at the beginning of the 11th year and at the turn of the 11th and 12th year. Conclusions: The unexpected shape of the histograms suggests that ambiguous interpretations of the vaccination schedule may be one of the causes of vaccination delays.